OSCILLATION THEOREMS FOR A CLASS OF SECOND ORDER NONLINEAR DIFFERENTIAL EQUATIONS WITH DAMPING - Rogovchenko, Yuri V.; Tuncay, Fatos (Mathematical Soc Rep China, 2009)
For a class of second order nonlinear differential equations with damping, efficient oscillation criteria are derived by refining the standard integral averaging technique. Examples are provided to illustrate the relevance of new theorems.
Keywords: Nonlinear differential equations; Damping term; Alternating coefficients; Second order; Asymptotic behavior; Oscillatory solutions; Integral averaging